(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
In the article a place and role of the functionally-communicative going for the studing of modern literary Ukrainian language in the process of the forming of a linguistic personality of future teacher-philologist are considered.